2019
DOI: 10.3390/ijerph16101826
|View full text |Cite
|
Sign up to set email alerts
|

Substance Use among Economically Disadvantaged African American Older Adults; Objective and Subjective Socioeconomic Status

Abstract: Purpose. This study investigated the effects of objective and subjective socioeconomic status (SES) indicators on two health behaviors, cigarette smoking and alcohol drinking, among African American older adults. Methods. This community-based study recruited 619 economically disadvantaged African American older adults (age ≥ 65 years) residing in South Los Angeles. Structured face-to-face interviews were conducted to collect data. Data on demographic factors (age and gender), subjective SES (financial difficul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 106 publications
2
41
0
Order By: Relevance
“…A recent study that analyzed this sample of older African American adults residing in South Los Angeles found that even though men smoked more than women, depressive symptoms had a stronger effect on women [4]. Current smoking use among this group is also associated with higher financial difficulties [2] and higher odds of drinking/binge drinking [3]. Smoking is a major modifiable risk factor for multiple illnesses, specifically, chronic respiratory conditions, among older African American adults living in these impoverished urban environments [54].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…A recent study that analyzed this sample of older African American adults residing in South Los Angeles found that even though men smoked more than women, depressive symptoms had a stronger effect on women [4]. Current smoking use among this group is also associated with higher financial difficulties [2] and higher odds of drinking/binge drinking [3]. Smoking is a major modifiable risk factor for multiple illnesses, specifically, chronic respiratory conditions, among older African American adults living in these impoverished urban environments [54].…”
Section: Discussionmentioning
confidence: 86%
“…African American intermittent smokers have a higher dependence, history of daily smoking, and smoke more cigarettes per day compared with Whites [70]. Within some minority populations, unhealthy behaviors, such as smoking and drinking, may act as coping behaviors for SES-related factors, such as financial difficulty [2].…”
Section: Discussionmentioning
confidence: 99%
“…Given the nature of the data collection, we defined our medication data collection as comprehensive. Data were gathered between 2015 and 2018 [10,[38][39][40][41][42][43].…”
Section: Comprehensive Evaluation Of Medicationsmentioning
confidence: 99%
“…Although all of LA County is experiencing an increase in homelessness, this is a more severe challenge in the poorest areas where AA individuals are more likely to lose their homes due to an inability to pay mortgage, rent, or property tax. Given poverty is concentrated in SPA6, homelessness has increased in this section of LA County [39].…”
Section: Sampling In An Economically Challenged Area and Sampling Framementioning
confidence: 99%
“…In this special issue, Lo et al [31] explored how far using illicit drugs, smoking cigarettes and drinking alcohol predicted sexual misconduct among Macau youths, while simultaneously adjusting for the effects of susceptibility to peer influence and school attachment/commitment. Assari et al [32] attempted to assess the impact of subjective and objective socioeconomic status on the cigarette smoking and alcohol use of older African Americans by controlling the effects of pertinent covariates, which included demographic factors (age and gender), living arrangement and family type, health insurance status, chronic medical conditions, self-rated health, sick days, depression and chronic pain. Muller et al [33] investigated changes in exercise and nicotine use among 1464 Norwegian prison inmates by classifying them into harmful and non-harmful substance use pre-incarceration groups, according to the Drug Use Disorders Identification Test (DUDIT) and the Alcohol Use Disorders Identification Test (AUDIT), both of which are commonly used by healthcare practitioners and researchers to assess the severity of illicit drug and intoxicant use.…”
Section: Substance Abuse and Its Types And Formsmentioning
confidence: 99%